Reasons for Differences in Educational Attainment and Employment Participation of Bidayuh Men and Women - Lyndon, Novel; Ismail, Maimunah (2007)
This article reports on reasons for differences in educational attainment and employment participation of Bidayuh men and women in the State of Sarawak, Malaysia. Data were gathered through in-depth interviews with eight selected respondents who were knowledgeable about Bidayuh community. The purpose was to find explanation for the differences between Bidayuh men‟s and women‟s educational attainment and employment participation. Qualitative data analysis was used for this study. Analysis shows that there are two reasons for Bidayuh women lag behind men in educational attainment. The reasons are cultural influence and historical background that Bidayuh women is said to have been long neglected in many aspects of educational opportunities. Reasons for the differences in employment participation between Bidayuh men and women are traditional gender division of labor, employer‟s bias on gender, and the lack of education, skills and training among women.